LINGUOCOLOR PICTURE OF THE UZBEK LANGUAGE - Kodirova Feruza Kahramanovna (Galaxy International Interdisciplinary Research Journal, 2023)
In the language system of a single collective, including folklore, proverbs, sayings, phraseological units, annals, oral and written speeches are a cultural pantry, which stores the knowledge, skills, material and spiritual values accumulated by the people.